The characterization and dissolution performances of spray dried solid dispersion of ketoprofen in hydrophilic carriers - Siok-Yee Chan; Yin-Ying Chung; Xin-Zi Cheah; Eryn Yen-Ling Tan; Joan Quah (Elsevier, 2015)
Solid dispersion is one of the most promising strategies to improve oral bioavailability of poorly soluble API. However, there are inconsistent dissolution performances of solid dispersion reported which entails further investigation. In this study, solid dispersions of ketoprofen in three hydrophilic carriers, i.e. PVP K30, PVPVA 6:4 and PVA were prepared and characterized. Physical characterization of the physical mixture of ketoprofen and carriers shows certain extent of amorphization of the API. This result is coinciding to evaluation of drug-polymer interaction using ATR-FTIR whereby higher amorphization was seen in samples with higher drug-polymer interaction. XRPD scanning confirms that fully amorphous solid dispersion was obtained for SD KTP PVP K30 and PVPVA system whereas partially crystalline system was obtained for SD KTP PVA. Interestingly, dissolution profiles of the solid dispersion had shown that degree of amorphization of KTP was not directly proportional to the dissolution rate enhancement of the solid dispersion system. Thus, it is concluded that complete amorphization does not guarantee dissolution enhancement of an amorphous solid dispersion system.